ENT 530 Business Model Canvas: Run Mart / Nurlaila Ruselan ... [et al.] - Ruselan, Nurlaila; Ahmad Hafidz, Saza Najiha; Zainuddin, Nur Atikah; Mohamed Nazim, Rasyiqa; Zulkafli, Nur Ain Nabihah (2021)
Run Mart is a mart that focuses on delivering fresh groceries to customers’ doors. The business started in early January 2021 and is managed by 5 Bumiputeras. The idea to name our business Run Mart came from the inspiration of delivering fresh groceries to our customers. We have chosen to do this business to conserve time and energy for all of us. In this era, going to crowded places to get an apple seems overrated. Run Mart is established to save the hassle with just a few clicks on the screen. We improve the visual experience that allows customers to shop online for groceries from their mobile devices at anytime and anywhere. This Business Model Canvas (BMC) will show us how to develop a new idea and improve the flow of doing business. It is also to assist us in obtaining a loan or grant from a financial institution. In addition, the content of the Business Model Canvas covers all parts of a new business to guide newcomers to this industry. This report also includes a SWOT analysis of competitors to get an idea of what precisely is a transaction in a business that has similar nature so that we are aware before anything happens later in the future. This research will also address the value of information in the Run Mart Business Model Canvas. Run Mart uses each of the nine columns in the Business Model Canvas. The canvas elements have included customer segments, value proposition, channels, customer relationship, revenue stream, key activities, key resources, key partnerships, and cost structure.